Stepwise approach for the control and eventual elimination of Taenia solium as a public health problem - Braae, U.C.; Gabriël, S.; Trevisan, C.; Thomas, Lian F.; Magnussen, P.; Abela-Ridder, B.; Ngowi, H.; Johansen, M.V. (Springer, 2019)
Background Taenia solium taeniosis/cysticercosis is a public health and agricultural problem, especially in low-income countries, and has been ranked the top foodborne parasitic hazard globally. In 2012, the World Health Organization published a roadmap that called for a validated strategy for T. solium control and elimination by 2015. This goal has not been met, and validated evidence of effective control or elimination in endemic countries is still incomplete. Measuring and evaluating success of control programmes remains difficult, as locally acceptable targets have not been defined as part of the 2012 roadmap nor from other sources, and the performance of tools to measure effect are limited. Discussion We believe that an international agreement supported by the tripartite World Health Organization, Food and Agriculture Organization of the United Nations, and World Organisation for Animal Health is needed to facilitate endemic countries in publicising SMART (Specific, Measurable, Achievable/attainable, Relevant, Time-bound) country-level control target goals. These goals should be achievable through locally acceptable adoption of options from within a standardised ‘intervention tool-kit’, and progress towards these goals should be monitored using standardised and consistent diagnostics. Several intervention tools are available which can contribute to control of T. solium, but the combination of these - the most effective control algorithm - still needs to be identified. In order to mount control efforts and ensure political commitment, stakeholder engagement and funding, we argue that a stepwise approach, as developed for Rabies control, is necessary if control efforts are to be successful and sustainable. Conclusions The stepwise approach can provide the framework for the development of realistic control goals of endemic areas, the implementation of intervention algorithms, and the standardised monitoring of the evaluation of the progress towards obtaining the control target goals and eventually elimination.